An integrated dynamic analysis method for simulating installation of single blades for wind turbines. (15th March 2018) - Zhao, Yuna; Cheng, Zhengshun; Sandvik, Peter Christian; Gao, Zhen; Moan, Torgeir
Abstract: Installation of blades for wind turbines is challenging due to large lifting height and high precision. Assessment of blade dynamic responses during installation needs advanced simulation tools which are limited at present. This paper aims at developing an integrated simulation tool SIMO-Aero for single blade installation for both onshore and offshore wind turbines. Based on the cross-flow principle, the aerodynamic model is established by accounting for the effect of wind turbulence and dynamic stall. Then it is coupled with SIMO to achieve the integrated simulation tool SIMO-Aero which can account for blade aerodynamics, vessel hydrodynamics and system mechanical couplings. The aerodynamic code is verified by code-to-code comparisons with HAWC2. Furthermore, SIMO-Aero is applied in case studies on the wind-induced dynamic responses of a DTU 10 MW blade during installation using a jack-up crane vessel which is assumed to be rigid, including the crane, and rigidly fixed to the seabed. The characteristics of system dynamic responses prior to mating the blade onto the hub are studied. It is shown that the blade motions are dominated by the pendulum motion. Critical parameters of the installation process are identified. The extreme responses of critical parameters are further studied under turbulent winds and wind gusts. Highlights: An integrated aero-hydro-mechanical simulation tool SIMO-Aero is developed for wind turbine blade installation. It has been verified by code-to-code comparisons. It is applied in a case study focusing on the wind-induced dynamic response of a DTU 10MW turbine blade during installation. It can also be used to study installation or removal of offshore wind turbine blades using either jack-up or floating crane vessels.